Hypercoagulability State in Patients with Chronic Obstructive Pulmonary Disease - Alessandri, Cesare; Basili, Stefania; Violi, Francesco; Ferroni, Patrizia; Gazzaniga, Pier Paolo; Cordova, Corrado; C.O.B.H. Group (Thrombosis and Haemostasis, 1994)
Since there is some clinical evidence that the clinical course of patients with chronic obstructive pulmonary disease (COPD) may be complicated by thrombosis in the pulmonary vessels, we studied whether a hypercoagulability state (HS) does occur in COPD. Plasma levels of prothrombin F1+2 fragment, a marker of thrombin generation, D-dimer, a marker of in vivo thrombin and plasmin activation, and fibrinogen were measured in 37 COPD patients and in 30 controls matched for sex and age. COPD patients had significantly higher values of F1+2 (p = 0.0001) and fibrinogen (p = 0.0005) than healthy subjects. The difference persisted after excluding smoking patients. F1+2 was not correlated with PaO2 (r = 0.02, p >0.05) and PaCO2 (p = 0.12, p >0.05). In six patients with stable COPD and F1+2 greater than 1.65 nM (mean + 2SD of controls) subcutaneous calcium-heparin therapy (5000 IU t.i.d. for 15 days) significantly reduced F1+2 (p = 0.03) and PaCO2 (p = 0.01). This study shows that COPD patients have an ongoing prothrombotic state which could potentially account for thrombosis occurring in pulmonary vessels. The effect of calcium-heparin treatment on clotting system activation and blood gas may suggest this treatment as potential candidate for prospective study in COPD patients.